An enhancement of vehicle security alarm system via SMS / Mohd Rosmanizam Hamad Rodzi - Hamad Rodzi, Mohd Rosmanizam (2006)
This project will focus on developing an enhancement of the vehicle alarm security system via SMS. The system will manipulate a mobile phone to send SMS (Short Message Service). Even though the SMS can be sent using the features available in the mobile, the objective of this project is to activate the SMS sending by the mobile phone using external program, connected physically to the mobile phone. The study of telecommunication is an interesting field because it involves digital signal processing, signal and systems, programming and more. This inspires people to improvise the technology into daily use. In this project, the technology of telecommunication, to be specific; SMS, is integrated or improvised to the present vehicle security system. Instead of human to human telecommunication, this system creates new entity which is machine to human telecommunication. This system is an upgrading and improving vehicle security system by integrating SMS features to alert vehicle owners whenever intrusion occurs. This project involves hardware and software parts construction and the integration of both parts to create the system. We succeed in achieving the objective and in fact, add another feature to the system which will initiates a call to the owner after sending the SMS. In the end of this project, we will document all the hardware and software development and provide a simulation model of the system.